Endovascular Repair of Complicated Type B Aortic Intramural Haematoma: A Single Centre Long Term Experience. (January 2022) - Tolboom, Herman; de Beaufort, Hector W.L.; Smith, Tim; Vos, Jan Albert; Smeenk, Hans G.; Heijmen, Robin H.
Abstract : Objective: To evaluate the efficacy of thoracic endovascular aortic repair (TEVAR) in the treatment of patients with complicated type B aortic intramural haematoma (IMH). Methods: A retrospective observational study of patients treated between January 2002 and December 2017 was performed. Complicated type B IMH was defined as persistent pain, rapid dilatation, presence of ulcer-like projections (ULPs), haemothorax, and other signs of (impending) rupture. Thirty day results and long term follow up outcomes were reported. Results: Thirty-nine patients were included for analysis (mean age 68 ± 8 years, 36% male). The thirty day mortality rate was 5%, stroke rate 10%, and re-intervention rate 3%. The median follow up duration was 49 months (25th – 75th percentile: 2 – 96 months). At 10 years, estimated freedom from all cause mortality was 66 ± 9%. During follow up, nine re-interventions were performed, leading to a 10 year estimated freedom from re-intervention rate of 72 ± 8%. Estimated freedom from aortic growth at 10 years was 85 ± 9%. Conclusion: Complicated type B IMH can be treated effectively by TEVAR, thus preventing death from aortic rupture. However, severe early post-operative complications, most importantly stroke, are of concern. Long term outcomes are excellent, although re-interventions are not uncommon, either for progression of proximal or distal aortic disease or due to stent graft related complications.